Forms and Intrinsic Elements of Bengkulu Folklore: A Structural Analysis of Ten Folk Narratives - Wirasti Fitria Afni; Kasmantoni Kasmantoni; Heny Friantary (Yayasan Darussalam Bengkulu, 2024)
Folklore plays an essential role in preserving cultural identity and transmitting values across generations, yet Bengkulu folklore remains underexplored in academic studies. This research aimed to analyze the forms and intrinsic elements of selected folktales from Bengkulu in order to identify their literary structures and cultural significance. A qualitative descriptive approach was employed, with data collected through documentation of ten Bengkulu folktales and analyzed using structural and literary methods to examine themes, plots, characters, settings, points of view, language styles, and moral messages. The findings revealed that Bengkulu folklore predominantly takes the form of legends and fairy tales that integrate historical memory, mythical imagination, and moral instruction. Intrinsic elements such as conflict-driven plots, royal and supernatural characters, and culturally rooted settings were identified as central features that convey values of justice, wisdom, resilience, and harmony with nature. These results indicate that folklore serves not only as a repository of cultural heritage but also as a pedagogical resource that can be integrated into character education and cultural literacy programs. The novelty of this study lies in its systematic literary analysis of Bengkulu folklore, which has been rarely addressed in prior research, thereby contributing new insights into Indonesian oral traditions and their relevance in modern education. The findings imply that folklore should be strategically incorporated into school curricula and community-based cultural preservation initiatives to strengthen national identity and foster moral development among younger generations.